THE RELATIONSHIP BETWEEN STUDENTS' LEARNING PREFERENCE AND STUDENTS’ ACHIEVEMENT IN ENGLISH SUBJECT AT MAN 2 POLEWALI MANDAR - Ramlah, Ramlah; Yaumi, Muhammad; Abubakar, Multazam (Journal of English Language and Culture, 2025)
This research aims to determine the extent of the significant correlation between students' learning preferences and their achievement in the second grade of MAN 2 Polewali Mandar. This study used a non-probability sampling technique to collect data on 26 samples from a total population 124. Researchers used a quantitative research approach with a correlation design. There are two types of instruments used in this research, namely the VARK questionnaire for learning preferences and rubric assessment for students' achievement. Research findings show that the correlation value of visual learning preference to students' achievement is 0.607. The correlation value for auditory learning preference to students' achievement is -0.316. The correlation value for read/write learning preference to students' achievement is -0.720, and the correlation value for kinesthetic learning preference to students' achievement is 0.227. Based on the data obtained, the researcher concluded that each learning preference component has a different level of correlation with student achievement in learning. The researcher hopes this study can be a reference and useful for further researchers who have the same focus of discussion, namely regarding student learning and achievement. The researcher also hopes that this study will help teachers pay more attention to the learning preferences of each of their students.